The monetary and fiscal implications of achieving debt sustainability ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Examines debt management and specifically the issue of debt sustainability, within the context of its linkages to monetary variables. Looks particularly at the issues facing developing economies, and tests modelling theory as to the determination of a sustainable level of debt, using data for The Bahamas.
Keywords: MONETARY POLICY